Epidermal Inclusion Cyst Presenting as a Palpable Scrotal Mass. (9th October 2012) - Correa, Andres F.; Gayed, Bishoy A.; Tublin, Mitchell E.; Parwani, Anil V.; Gingrich, Jeffrey R.
Abstract : We report a scrotal epidermal inclusion cyst located outside the median raphe which a rare entity in the absence of trauma and few cases have been reported. 47 year old male presents with a complaint of right sided testicular swelling and discomfort. On examination a 3 cm mass was palpated between the scrotum and the medial thigh on the subcutaneous tissue with a positive slip sign. Complete surgical excision of the cyst was performed. Histopathology confirmed epidermal inclusion cyst with no evidence of malignancy.